Analgesic Activity Combination of Dry Extract of Meniran Leaves (Phyllanthus niruri L.) and Moringa Leaves (Moringa oleifera L.) Using the Chemical Induction Method: Invivo Study - Dian Arsanti Palupi; Sugiarti, Lilis; Eni Yulianti (HM Publisher, 2024)
Analgesics are drugs that selectively reduce pain in the central nervous system or peripheral pain mechanisms without significantly changing consciousness. This study aims to determine the analgesic activity of a combination of dry extracts of meniran leaves (Phyllanthus niruri l.) and moringa leaves (Moringa oleifera l.) against Swiss Webster rats with chemical induction methods. This research proves the presence of secondary metabolite content in the dry extract of meniran leaves and moringa leaves which have analgesic activity. The research used 30 male Swiss Webster rats divided into 5 groups. Group 1 is the negative control (CMC-Na 0.5%), group 2 is the positive control (diclofenac Na), group 3 (Dry extract of meniran leaves), group 4 (Dry extract of moringa leaves) and Group 5 (Combination of dry extracts). meniran and moringa leaves). Each was given 1 mL of 1% acetic acid induction chemical stimulation, then the writhing response was observed and recorded at 5-minute intervals for 30 minutes. The results showed that the K3 group combined dry extract of meniran leaves (Phyllanthus niruri L.) and moringa leaves (Moringa oleifera L) is not statistically significantly different from the positive control diclofenac sodium, p-value = 0.183. In conclusion, dry extract of meniran leaves (Phyllanthus niruri L.) and Moringa leaves (Moringa oleifera L.) has been proven to contain secondary metabolites of flavonoids, alkaloids, tannins, and saponins which have analgesic activity.